(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
Independence of the Republic and Improving the content of vocational education, which is responsible for the formation of socio-economic policy in line with modern requirements of a market economy, training highly qualified junior specialists and ensuring the effectiveness of this process. This task is reflected in a number of laws and regulations, in particular in the National Training Program, the system and content of training in the social and economic life of the country. Reconstruction based on the prospects of economic development, the needs of society, modern achievements of science, culture, engineering and technology clear goal-oriented guidelines and principles in the example reflected in the appearance